2020
DOI: 10.21203/rs.3.rs-77157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metatranscriptomics to characterize respiratory virome, microbiome, and host response directly from clinical samples

Abstract: We developed a metatranscriptomics method that can simultaneously capture the respiratory virome, microbiome, and host response directly from low-biomass clinical samples. Using nasal swab samples, we have demonstrated that this method captures the comprehensive RNA virome with sufficient sequencing depth required to assemble complete genomes. We find a surprisingly high-frequency of Respiratory Syncytial Virus (RSV) and Coronavirus (CoV) in healthy children, and a high frequency of RSV-A and RSV-B co-infectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Total RNA from the nasopharyngeal swab samples was extracted and further processed as previously described [10]. After quality-based trimming and removal of human and bacterial rRNA reads, we had an average of 98,120,791 (740,58,180 -median) human reads and an average of 2,263,290 (848,478 -median) microbiome reads.…”
Section: Metatranscriptome Captured the Nasal Viromementioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA from the nasopharyngeal swab samples was extracted and further processed as previously described [10]. After quality-based trimming and removal of human and bacterial rRNA reads, we had an average of 98,120,791 (740,58,180 -median) human reads and an average of 2,263,290 (848,478 -median) microbiome reads.…”
Section: Metatranscriptome Captured the Nasal Viromementioning
confidence: 99%
“…The nasal swab samples in the self-collection kit (FLOQSwabs, Copan Diagnostics Inc.) were vortexed for 2 minutes, then an aliquot of 250µL nasal swap sample was used for RNA extraction. The total RNA from these samples were extracted as describe previously [10]. In brief, 250µL aliquot from the nasal swab sample was homogenized in 600µL QIAzol (Qiagen) and 500µL of 2.0 mm zirconium oxide beads (Next Advance, Inc. Cat: ZROB05) using a Bullet Blender homogenizer (BB24-AU, Next Advance, Inc).…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 Testing By Q...mentioning
confidence: 99%
See 1 more Smart Citation
“…NGS can fulfill those requirements. Shotgun NGS generates sequence information from every molecule in a sample (e.g., nasal swab, saliva, blood), and has shown to be applicable for human infectious disease diagnostic tests (7)(8)(9), respiratory infections (10), and universal pathogen detection (11)(12)(13)(14)(15). Prior to the pandemic, an NGS-based study involving a population of ~1,000 pangolins from a wet market in Wuhan China, identified coronavirus infections in over 70% of the pangolin samples tested (16).…”
Section: Introductionmentioning
confidence: 99%